Rancang Bangun Antenna Mikrostrip Peripheral Slits Linear Array Untuk Aplikasi Wi-Fi - Syah Alam; I Gusti Nyoman Yogi Wibisana; Indra Surjati (Jurnal Rekayasa Elektrika, 2017)
Wireless Fidelity (Wi-Fi) is the modern telecommunication technology nowadays being so widely used and developed at operating frequency of 2.4 GHz, that needs microstrip antenna as best suited supporting means for transmitting and receiving data signals as well at its wave transceiver subsystem.  The proposed antenna design were consists of four elements rectangular patch antenna with peripheral slits technique arranged in a linear array of 2x2 operating at the frequency of 2.4 GHz until 2.5 GHz. In addition to that, the feeding technique used in this research is microstrip fed line. The simulation from this research resulted in reducing the size of related antenna dimension up to 17% compared to that of four elements array without peripheral slits. It is also apparent that the bandwidth of the proposed antenna is 320 MHz (2.253 GHz–2.573 GHz) which is equivalent to bandwidth increase percentage of 13.07%, The simulation results in the center of frequency 2.448 GHz obtained return loss of -26.14 dB with a VSWR of 1.104. The measurement results obtained bandwidth of the proposed antenna is 150 MHz (2.424 GHz–2.574 GHz) which is equivalent to 12% increase of bandwidth percentage. The results of measurements process at the center of frequency 2.448 GHz obtained value of return loss of -16.88 dB with  VSWR of 1.304.